Green Practices and Corporate Sustainability Value In Agroindustry Company X, North Sumatra - Astuti; Rosdita Indah Yuniawati; Dede Yusuf Maulana; Helda Jaya Puspita (International Journal of Management and Business Economics, 2026)
This study examined how green practices influence corporate sustainability value in Agroindustry Company X in North Sumatra, Indonesia. The study used a quantitative descriptive case-study design based on annual reports, sustainability-related documents, direct observation, and structured interviews with three managers for the 2020-2024 period. The green practice index was constructed from four dimensions: environmental management, energy efficiency, waste management, and green purchasing. Each dimension was scored from 1 to 25 and then summed into a 0-100 index. Sustainability value was constructed as a 0-1 composite ratio from normalized economic, social, and environmental indicators. Data were analyzed through trend analysis and simple linear regression. The green practice score increased from 52 in 2020 to 81 in 2024, while sustainability value increased from 0.48 to 0.79. Regression results show a positive relationship between green practices and sustainability value, with a coefficient of 0.0109 and R² of 0.990. Because the dataset used five annual observations from one firm, the result is interpreted as exploratory case evidence. The study shows that systematic environmental practices can support long-term value creation through efficiency, transparency, and stakeholder confidence